Nutritional Composition and Sensory Quality of Packaged Ofe-Owerri: A Major Traditional Soup in Nigeria - Oyewale, Mary B.; Seidu, Kudirat T.; Ogunbusola, Eunice M.; Osundahunsi, Oluwatooyin F.; Ogunwa, Tomisin H.; Akele, Olatunbosun; Adejoro, Damola O. (Current Nutrition & Food Science, 2020)
Background: Ofe-Owerri is an expensive traditional soup in Nigeria, prepared using Oha (Pterocarpus soyauxi), Ukazi (Gnetum africanum), Uziza (Piper guineense) and cocoyam (Colocasia esculanta) as the major vegetables. The soup is highly celebrated for its traditional therapeutic and nutritional potentials. Objective: In this study, we assessed the proximate and mineral components, sensory and microbial qualities of the Ofe-Owerri soup in a cooked and packaged form. Antioxidant status and phytoconstituents of the major vegetables of the soup were also determined. Methods: Established methods were used as previously reported in the literature. Results: Calcium was the most concentrated mineral, whereas lead was absent. High moisture (63.45%), crude protein (14.60%) and fat (13.27%) were found in the soup. The major ingredients (vegetables) used to prepare Ofe-Owerri contain phytochemicals such as phenolic compounds and saponins, and showed potent antioxidant activity in various in vitro models, with uziza displaying the highest scavenging activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical. The vegetables exhibit reductive capacity against oxidants, and chelation of metallic free radicals. There was no significant difference (p≤0.05) in the sensory parameters of Ofe-Owerri soup kept frozen in foil and plastic containers, respectively, for 21 days. Conclusion: This study showed that Ofe-Owerri is a good dietary source of nutrients and possesses phytoconstituents with potential beneficial health effects. When properly packaged, the soup can be stored safely for up to three weeks.
Keywords: sensory quality